The effect of ubiquitous learning management system using imagineering to enhance learning achievement and multimedia creation skill for upper secondary school - Pannathat Champakul; Suwanna Bengthong; Kanchana Boonphak (My University, 2022)
The research objectives were: (1) to analyze the efficiency of the Ubiquitous Learning Management System using Imagineering; (2) to compare the student's learning achievement and student's multimedia creation skill between experimental group and control group.The samples consisted of 120 grade 11 students from three classrooms who enrolled in the Digital multimedia course, Liberal arts structure plan at Satri Samutprakarn School, in the second semester of the academic year 2019, selected by using cluster random sampling and randomizing the classrooms into 3 groups by lottery method.The first classroom was 40 students who were tested for efficiency of the Ubiquitous Learning Management System using Imagineering (E1/E2).The second was 40 students who were an experimental group.The third was 40 students who were a control group.The research instruments were 3 sets of:(1) the Ubiquitous Learning Management System using Imagineering;(2) the assessment form of multimedia creation skill; and (3) The achievement test.Statistics for data analysis included Mean, Standard Deviation and Hypothesis testing by One-way Multivariate Analysis of Variance (One-way MANOVA).The research results found that the efficiency of the Ubiquitous Learning Management System using Imagineering (E1/E2) was 81.00/ 80.15.The learning achievement and the multimedia creation skill of the experimental group yielded a higher score than the control group at the statistical significance level of .05.
Keywords: Education and Learning Interventions